(3GdefgGL aj TQM UMjM eSde Hf GdMLGLs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA cJGH GdWgGQI , HHGH GdPcQ GdeSJMH YbH GdhVhA s
(3BNQgG (B:s
(3jfJgi HcJGH aVGFd GdbQBf heG jJYdb Hg , HHGH UdGI GdNha Hbhdg (B: (3acGf Gdfi Udi Gddg Ydjg hSde efadkG ai GdKGfjI hge eaJQVhf hESJOd Hg GdTGaYi hCUMGHg Ydi LhGR UdGI GdeaJQV Nda GdeJfad hGddg CYde HGdUhGH s
(3ef JMHjS GdSdWGf CHj GdYHGS Ydi LGeY GdCfOdS YGe (B798 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs